NEOLIBERALISME DALAM PERSPEKTIF ISLAM - Hendri Hermawan Adinugraha (MEDIA, 2012)
The Neoliberalism for some groups was considered superior to other economic systems, but the reality is the ideology fails to provide for the people welfare and has caused excessive economic inequality. Neoliberalism is the current and emerging economic paradigm characterized by the conventional paradigm that seeks to separate the economic activity of all religious values â€‹â€‹and the release of government intervention through free markets, privatization, and globalization. Unlike the Islamic values â€‹â€‹contained in the Qurâ€™an and Sunnah, which has been able to become the main cornerstone of an economic system, the Islamic economic system. Islam teaches a balance between individual economic freedom with justice and the common good. Because it includes outlook and way of life as a whole as well (kÄffah) as Islam has a goal of creating an economic system with the principles of justice (al-â€˜adl) for all groups. While neoliberalism is an economic ideology that is based on capitalism, and when Neoliberalism applied in the economic system, it will caused more harm than good and benefit.